2021
DOI: 10.3390/su132212555
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Education for Sustainable Development Competencies in Teacher Education

Abstract: The aim of this study is to provide a comprehensive overview of the publications focused on integrating education for sustainable development (ESD) competencies into teacher education during the last decade, in an endeavour to identify which competencies have been considered in the literature as key competencies for reorienting teacher education towards sustainability as well as explore the suggested assessment tools and approaches to integrate these competencies into teacher education programmes. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The study reveals that training of teachers and pedagogical techniques play a key role in knowledge transfer for sustainability. Imara (2021) give a summary of incorporating ESD competencies into teacher education, which shows the success and the issues in the latter's mainstreaming. It highlights a gap in the development of a unified framework for ESD competencies in teacher education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study reveals that training of teachers and pedagogical techniques play a key role in knowledge transfer for sustainability. Imara (2021) give a summary of incorporating ESD competencies into teacher education, which shows the success and the issues in the latter's mainstreaming. It highlights a gap in the development of a unified framework for ESD competencies in teacher education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' academic feat from a variety of backgrounds is therefore a matter of tutor qualities. Imara, K., & Altinay, F. (2021) found that teacher education within the last decade has largely focused on identifying competences that have been observed and measured in much literature and are crucial to reimagining teacher education in terms of its sustainability and exploring assessment tools and approaches to the integration of these competences into teacher education.…”
Section: Basic Tutoring Competencesmentioning
confidence: 99%
“…Approaches to sustainable higher education may vary as well as the criteria used to assess how effectively sustainability is integrated. Scholarly work indicates such criteria as progress [34,35] or spectrum [36] of students' or teachers' ESD competencies [37,38] and these are assessed most commonly; however, it is recommended that the institution implements and assesses the following practices on the path to sustainability: (1) institution's mission and purpose for the sustainability problem; (2) the inclusion of the concept of sustainability in all academic disciplines; (3) whether students learn about institutional values and practices for the development of a sustainable ecosystem; (4) institutional support for activities that emphasize sustainability; and (5) collaboration forming partnerships at a national and international level to enhance sustainability [32].…”
Section: An Overview Of the Study Areamentioning
confidence: 99%